The establishment of circumstances and evidences of an accident and their appliction in research - Tautkus, Arūnas; Jurkauskas, Algirdas (Transport, 2003)
An accident depends on a lot of factors and circumstances. The estabilishment of factors, different evidences and circumstances are very important for research. Some important evidences are fixed when we make photos, do the the measurements of the deformation of means of transport, do the measurements of sliding and of stopping, estimate the condition of road and weather, driver’s and pedestrian’s actions, do cross-examination of witnesses and so on. We often have no result even if we know the main circumstances of the accident. So we need some engineer countings for the modelling of various situations. The method of linear momentum is presented in this article. It is used for the counting of parameters of accidents. The accident diagram gives information for us. We can do the research of an accident with the help of this method and software. So the research into the collision of cars was done with the help of this method and software. First Published Online: 19 Dec 2011